Pendampingan Penerapan School Well Being Pada Santri Dalam Upaya Pencegahan Kekerasan Pada Pondok Pesantren - Ulin Ni'mah Rodliya Ulfah; Erna Nurkholida; Laili Paulina Choirunnisak (LP3M IAIFA Kediri, 2025)
The phenomenon of violence within Islamic boarding schools (pesantren) has become a serious concern in Islamic education. This community service project aimed to implement the concept of school well-being to prevent violence against students (santri), particularly at Hidayatut Thulab Islamic Boarding School, Petok Mojo, Kediri Regency. Using the Participatory Action Research (PAR) method, the program included several stages such as problem identification, training for boarding school administrators, psychological and clinical mentoring, as well as evaluation and monitoring. The training focused on six dimensions of psychological well-being as defined by Ryff: autonomy, environmental mastery, personal growth, positive relations with others, self-acceptance, and purpose in life. The results from questionnaire distribution indicated that most students demonstrated a positive level of psychological well-being, reflecting the success of the mentoring program in creating a safe, inclusive, and mentally supportive learning environment. This activity also encouraged a cultural transformation within the pesantren toward a more humane and responsive approach to students' developmental needs.